Investigation of shallow subsurface soil for engineering construction: A case study of Etioro Akoko, Southwestern Nigeria. Issue 1 (31st December 2023) - Ogunribido, Tolulope Henry; Ale, Temitayo Olamide; Uko, Emeka Kingsley; Ale, Taiwo Ayomide
Abstract: For sustainable development of Etioro Akoko, Southwestern Nigeria, soil materials must meet and exceed the requirements of a good tropical environment soil. This study is aimed at using geotechnical and geophysical investigations to evaluate the subsoil for pre- and post-engineering construction and to achieve sustainable groundwater development. The geotechnical analyses are grain size analysis, Atterberg, linear shrinkage, specific gravity, CBR and compaction tests, while electrical resistivity method was used for geophysical investigation. The geotechnical analysis of liquid limit, plastic limit, plasticity index, linear shrinkage, grain size analysis, specific gravity, CBR and compaction tests range from 24.0%–40.8%, 19.3%–23.7%, 4.3%–17.4%, 1.4%–9.3%, 2.58–2.62, 30%–46%, 1496 kg/m 3 –1742 kg/m 3 and 10%–14.2%, respectively. For the electrical resistivity approach, six traverses in an east–west orientation were created. Four distinct layers were identified, and they are top soil, weathered layer, slightly weathered layer and bedrock. Two wells of moderate to good yield were identified from the different fractures located. Atterberg limit tests and grain size analysis of the soil samples showed that these soil samples met the requirements for a good soil in Nigeria. The CBR and MDD values showed that they are suitable for subgrade courses. We reject the null hypothesis for statistical analysis between the mean resistivity values of the six traverses and the geotechnical properties of the soil and also the ANOVA statistic between resistivity values and the six traverses, while we accept the null hypothesis for variables between geotechnical data.